Nap1l1 Controls Embryonic Neural Progenitor Cell Proliferation and Differentiation in the Developing Brain - Huimin Qiao (Cell Reports, 2018)
Summary: The precise function and role of nucleosome assembly protein 1-like 1 (Nap1l1) in brain development are unclear. Here, we find that Nap1l1 knockdown decreases neural progenitor cell (NPC) proliferation and induces premature neuronal differentiation during cortical development. A similar deficiency in embryonic neurogenesis was observed in Nap1l1 knockout (KO) mice, which were generated using the CRISPR-Cas9 system. RNA sequencing (RNA-seq) analysis indicates that Ras-associated domain family member 10 (RassF10) may be the downstream target of Nap1l1. Furthermore, we found that Nap1l1 regulates RassF10 expression by promoting SETD1A-mediated H3K4 trimethylation at the RassF10 promoter. Nap1l1 KO defects may be rescued by RassF10 overexpression, suggesting that Nap1l1 controls NPC differentiation through RassF10. Our findings reveal an essential role for the Nap1l1 histone chaperone in cortical neurogenesis during early embryonic brain development. : Nap1l1 plays essential roles in embryonic neurogenesis, including the proliferation and differentiation of neural progenitors. Qiao et al. find that Nap1l1 regulates RassF10 through SETD1A-mediated H3K4me3 of the RassF10 promoter. Keywords: neural progenitor cell, neural differentiation and proliferation, cortex development, gain of function, loss of function, histone chaperone, Nap1l1, RassF10, H3K4me3